ACUTE NEGATIVE AFFECT RELIEF FROM SMOKING DEPENDS ON THE AFFECT SITUATION AND MEASURE, BUT NOT ON NICOTINE - Perkins, Kenneth A. (Biol Psychiatry, 2010)
BACKGROUND: Smoking acutely relieves negative affect (NA) due to smoking abstinence but may not relieve NA from other sources, such as stressors. METHODS: Dependent smokers (N=104) randomly assigned to one of three smoking conditions (nicotine or denic cigarettes, or no smoking) completed four negative mood induction procedures (one per session): 1) overnight smoking abstinence, 2) challenging computer task, 3) public speech preparation, and 4) watching negative mood slides. A fifth session involved a neutral mood control. The two smoking groups took 4 puffs on their assigned cigarette, and then smoked those same cigarettes ad libitum during continued mood induction. All subjects rated their level of NA and positive affect (PA) on several measures (Mood Form, PANAS, Stress-Arousal Checklist, and STAI-state). They also rated craving and withdrawal. RESULTS: NA relief from smoking depended on the NA source (i.e. mood induction procedure) and the affect measure. Smoking robustly relieved NA due to abstinence on all 4 measures, but only modestly relieved NA due to the other sources and typically on only some measures. Smoking’s effects on PA and withdrawal were similar to effects on NA, but relief of craving depended less on NA source. Smoking reinforcement only partly matched the pattern of NA relief. Few responses differed between the nicotine and denic smoking groups. CONCLUSIONS: Acute NA relief from smoking depends on the situation and the affect measure used but may not depend on nicotine intake. These results challenge the common assumption that smoking, and nicotine in particular, broadly alleviates NA.